An optimization model for network design in disaster relief planning - Kevin Palomino; Carmen Berdugo-Correa; David García-Barrios (Revista Facultad de Ingeniería Universidad de Antioquia)
A model was created to optimize aid relief efforts by identifying the best location to set up shelters. This model, which was developed using a mixed-integer linear program - MILP, considers the availability of resources and the cost of different locations, as well as constraints that must be met to ensure timely aid delivery. A solution involving the use of branch-and-cut algorithm with the help of GeoJSON API and Python code was proposed. Additionally, a study was conducted to assess the impact of the model by analyzing the water supply during a natural disaster in Mocoa, Colombia in 2017. The results of the study  showed that the model had a positive impact on reducing the distance resources had to travel, increasing the satisfaction of shelter needs, and decreasing the costs of implementation.